Co-autodisplay of Z-domains and bovine caseins on the outer membrane of E. coli - Yoo, Gu; Saenger, Thorsten; Bong, Ji-Hong; Jose, Joachim; Kang, Min-Jung; Pyun, Jae-Chul (ELSEVIER SCIENCE BV, 2015)
In this work, two proteins, Z-domains and bovine casein, were autodisplayed on the outer membrane of the same Escherichia coli cells by co-transformation of two different autodisplay vectors. On the basis of SDS-PAGE densitometry, Z-domains and bovine casein were expressed at 3.12 x 10(5) and 1.55 x 10(5) proteins/E. coli cell, respectively. The co-autodisplayed Z-domains had antibody-binding activity and the bovine casein had adhesive properties. E. coli with co-autodisplayed proteins were analyzed by fluorescence assisted cell sorting (FACS). E. coli with co-autodisplayed Z-domains and bovine casein aggregated due to hydrophobic interaction. For application to immunoassays, the Z-domain activity was estimated after (1) immobilizing the E. coli and (2) forming an OM layer. E. coli with co-autodisplayed two proteins that were immobilized on a polystyrene microplate had the same antibody-binding activity as did E. coli with autodisplayed Z-domains only. The OM layer from the cotransformed E. coli had Z-domains and bovine casein expressed at a 1:2 ratio from antibody-binding activity measurements. (C) 2015 Elsevier B.V. All rights reserved.
Keywords: ESCHERICHIA-COLI; SURFACE DISPLAY; RECOMBINANT PROTEINS; SPR BIOSENSOR; IMMUNOASSAY; ELISA